Indigenous knowledge of Zigi community and forest management decision-making: a perspective of community forest interaction - Fadhilia, Bwagalilo; Liwa, Evarist; Shemdoe, Riziki (JNRD - Journal of Natural Resources and Development, 2015)
Indigenous knowledge (IK) regarding forests has existed for a long time and has defined community’s forests interaction in various areas. This interaction has resulted in knowledge developed by indigenous communities that has been used to manage their interaction with the forests. However, IK is often regarded as invalid and unreliable to use in forest management and its value has been eroded and replaced with western scientific knowledge for both production and conservation forest management objectives. However, despite the application of modern scientific knowledge, forest status continues to decline. This paper aims to explore IK held by communities in the Zigi catchment in Tanzania and assess the influence of this form of knowledge on forest management. The study used focus group discussions to explore IK related to forest management from communities living adjacent to forest reserves and a checklist questionnaire to assess the level of use of IK in forest management at different levels of decision-making. The results reveal several IK and practices related to forests in this region. However, there is minimal evidence of consideration of this IK in forest management decision-making. This paper recommends that a serious review of IK related to forests is undertaken in Tanzania and that mechanisms are developed to integrate this form of knowledge with western scientific forest management in order develop a more holistic approach to sustainable forest management.